"Native Huts" St. Lucia, B.W.I - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2012)
A group of men, women and children stand outside a cluster of houses with thatched roofs.
Landscape; black and white
Keywords: Huts; Wooden buildings; Thatched roofs; Men; Women; Children; Postcards; Trees